Bolus potassium in frustrated ventricular fibrillation storm. Issue 2 (25th November 2019) - Elmahrouk, Ahmed F.; Elghaysha, Ehab; Arafat, Amr A.; Edrees, Azzahra; Aluthman, Uthman; Jamjoom, Ahmed A.
Abstract: Background: Ventricular fibrillation (VF) is a well‐known ominous complication of ischemic heart disease. While firmly structured algorithms have been developed for its management, yet its mortality rate remains high. Case Presentation: This is a case report of a 46‐year‐old gentleman who was a victim of recurrent cardiac arrest in the ward while awaiting coronary artery bypass grafting (CABG) surgery. Emergency CABG was performed, intraoperatively he experienced recurrent VF which was reverted by direct current cardioversion‐Defibrillation. He was sent to the Cardiac Surgery Intensive Care Unit (CSICU) with an open chest on extracorporeal membrane oxygenation (ECMO) support and an intra‐aortic balloon pump. Postoperatively in CSICU he still experienced malignant ventricular arrhythmia with dropping of ejection fraction to less than 10%. The last few episodes of VF were lengthy, lasting more than an hour (while on ECMO support) with the failure of various antiarrhythmic medications to abort them. Eventually, a decision was made to give him 20 mmol boluses of potassium chloride (KCl) intravenously aiming at introducing a state of asystole, but the rhythm changed to sinus rhythm. Conclusions: This report highlighted the fact that optimum management of VF is still lacking and necessitates more studies. The appropriate effective dose of potassium replacement during VF might need to be reconsidered in patients with persistent VF.